A fluorescent molecular sensor based on 1, 8-naphthalimide for sensitive and rapid detection of human serum albumin. (December 2022) - Zhang, Meijuan; Cao, Jian; Huang, Cuiping; Liu, Mingming; Li, Yanan; Wang, Chuanxiao; Tu, Yajing
Abstract: Human serum albumin (HSA) accounts for 60% of total plasma protein and is closely related to life-threatening diseases. In this strategy, three fluorescent sensors of Nap-OH, Nap-C and Nap-NO2 based on twisted intramolecular charge transfer (TICT) are designed and synthesized for detecting of HSA, and the effect of electron donating-withdrawing groups of sensors on the detection of HSA is studied. After added HSA, the fluorescent emission of Nap-NO2 is turned on at 630 nm, and the color changed from colorless to pink. Nap-NO2 is characterized by a 14.06-fold increase in fluorescence emission and has high sensitivity, good selectivity, fast response, and good stability. Nap-NO2 could effectively distinguish HSA from other proteins, including bovine serum albumin (BSA). Drug competition experiments are performed that Nap-NO2 can bind to the IB domain of HSA, avoiding the interference of commonly used drugs. Nap-OH, Nap-C and Nap-NO2 can also be used for viscosity detection. Highlights: The 1, 8-naphthalimide was connected with the pyridinyl group by a double bond to form "donor-π-acceptor (D-π-A)" structure. The D-π-A structure was strategy tuned by fusing different electron donating-withdrawing groups on the pyridinyl group. A good linear relationship of fluorescent emission intensity was obtained with the HSA concentration range of 0–20 μg/mL. The hydrophobic pocket of HSA provides high steric hindrance to induce the increasing fluorescent emission of sensor.